From Challenge to Insight: The Effectiveness of a Cognitively Oriented Psychological Intervention on Reflective Functioning in Female Teachers of Students with Autism Spectrum Disorder - Karimiha, Mohsen; Jenaabadi, Hossein; Alisofi, Allah Nazar (Psychological Research in Individuals with Exceptional Needs, 2026)
The present study was conducted to examine the effectiveness of a cognitively oriented psychological intervention on reflective functioning in female teachers of students with Autism Spectrum Disorder. The present research employed a quasi-experimental design with a pretest–posttest format, including a control group and a two-month follow-up period. The statistical population consisted of all female teachers of students with autism spectrum disorder in the city of Qazvin during the 2025–2026 academic year. From this population, 34 participants were selected using convenience sampling and were then randomly assigned to an experimental group (n = 17) and a control group (n = 17). Participants in both groups were assessed across three stages using the Reflective Functioning Questionnaire (RFQ-8) developed by Peter Fonagy et al. (1997). In the present study, individuals in the experimental group received 10 sessions of intervention, whereas the control group received no intervention. Data were analyzed using repeated measures analysis of variance (ANOVA) with SPSS version 25. The findings of data analysis indicated that the cognitively oriented psychological educational intervention had a statistically significant effect on reflective functioning (p < .05). Furthermore, the results demonstrated that the significant effect of this therapeutic approach on reflective functioning was sustained at the follow-up stage (p < .05) In conclusion, it can be inferred that a cognitively oriented psychological intervention, as an effective method, can lead to improvements in teachers’ reflective functioning. Therefore, the application of such an approach may be considered a valuable strategy for enhancing the mental functioning of teachers working with this group of students.